2017
DOI: 10.1021/acs.est.6b06169
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Ternary Cd–Cu–Ni and Cd–Ni–Zn Mixtures to Daphnia magna: Dominant Metal Pairs Change along a Concentration Gradient

Abstract: Multiple metals are usually present in surface waters, sometimes leading to toxicity that currently is difficult to predict due to potentially non-additive mixture toxicity. Previous toxicity tests with Daphnia magna exposed to binary mixtures of Ni combined with Cd, Cu, or Zn demonstrated that Ni and Zn strongly protect against Cd toxicity, but Cu–Ni toxicity is more than additive, and Ni–Zn toxicity is slightly less than additive. To consider multiple metal–metal interactions, we exposed D. magna neonates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Extensive literature has reported the effect of additive toxicity of chemicals mixtures in marine invertebrates reproductive success and mortality ( Cooper, Bidwell & Kumar, 2009 ; Hagopian-Schlekat, Chandler & Shaw, 2001 ; Picone et al, 2018 ). However, these effects highly depend on the type of interaction (metal-metal, metal-organic, organic-organic) and on the concentration of each compounds in the mixture, which can either trigger synergistic, antagonistic, or non-interactive toxicities ( Gauthier et al, 2014 ; Nys et al, 2016 ; Traudt, Ranville & Meyer, 2017 ). A recently published framework for ecological risk assessment ( Nys et al, 2018 ) was developed to better characterize the bioavailability of metal mixtures, based on a sensitive species distribution model.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature has reported the effect of additive toxicity of chemicals mixtures in marine invertebrates reproductive success and mortality ( Cooper, Bidwell & Kumar, 2009 ; Hagopian-Schlekat, Chandler & Shaw, 2001 ; Picone et al, 2018 ). However, these effects highly depend on the type of interaction (metal-metal, metal-organic, organic-organic) and on the concentration of each compounds in the mixture, which can either trigger synergistic, antagonistic, or non-interactive toxicities ( Gauthier et al, 2014 ; Nys et al, 2016 ; Traudt, Ranville & Meyer, 2017 ). A recently published framework for ecological risk assessment ( Nys et al, 2018 ) was developed to better characterize the bioavailability of metal mixtures, based on a sensitive species distribution model.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature has reported the effect of additive toxicity of chemicals mixtures in marine invertebrates reproductive success and mortality (Cooper et al 2009;Hagopian-Schlekat et al 2001;Picone et al 2018). However, these effects highly depend on the type of interaction (metal-metal, metal-organic, organic-organic) and on the concentration of each compounds in the mixture, which can either trigger synergistic, antagonistic, or non-interactive toxicities (Gauthier et al 2014;Nys et al 2016;Traudt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In CA, substances have a similar mode of action, and in IA (also known as response addition), substances have different modes of action. Nickel in the aquatic compartment, when combined in binary or ternary mixtures with other metals, does not necessarily exhibit a strictly response-additive toxicity in invertebrates or fish [235][236][237] and responses depend on the other metals present. For instance, Traudt et al [236] found that acute Ni + Cd mixtures resulted in less-than-additive toxicity to D. magna neonates, while Ni + Cu mixtures resulted in greater-than-additive toxicity and Ni + Zn mixtures resulted in response-additive toxicity.…”
Section: Mixturesmentioning
confidence: 99%